2017
DOI: 10.33546/bnj.95
|View full text |Cite
|
Sign up to set email alerts
|

Roselle Flower (Hibiscus Sabdariffa) in the Treatment of Hypertension in Postpartum Mothers

Abstract: Background: Roselle flower (Hibiscus sabdariffa) has been used as a food and herbal drinks, in hot and cold beverages, as a herbal medicine.Objective: To examine the effect of consuming roselle dried flower petals on changes in maternal hypertensive blood pressure during postpartum period.Methods: This was a quasi-experimental study with non-equivalent control group design conducted in 2016. There were 30 samples recruited using consecutive sampling with 15 samples in the intervention group and control group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
(2 reference statements)
1
6
0
1
Order By: Relevance
“…It is similar to a previous study, which revealed that nonadherence to medication because of the use of traditional medicine is one of the barriers in hypertension management (Gebrezgi et al, 2017). It is undeniable that people in Indonesia not only believe in conventional medicine (Ritonga et al, 2017) but also in shaman for the medication (Sherliawati, 2014). It is in line with a study in rural Yogyakarta, Indonesia, which also found that the patients with hypertension tend to have the preference to manage hypertension on their own, especially to use traditional or alternative medicines and herbs, such as cucumber, avocado leaves (Rahmawati & Bajorek, 2018), aloe vera (Yuliawati et al, 2021, celery leaves (Isnainy et al, 2021), cupping therapy (Darmawan et al, 2017), acupuncture (Hidayah et al, 2021), and others to replace the prescribed medication.…”
Section: Discussionsupporting
confidence: 86%
“…It is similar to a previous study, which revealed that nonadherence to medication because of the use of traditional medicine is one of the barriers in hypertension management (Gebrezgi et al, 2017). It is undeniable that people in Indonesia not only believe in conventional medicine (Ritonga et al, 2017) but also in shaman for the medication (Sherliawati, 2014). It is in line with a study in rural Yogyakarta, Indonesia, which also found that the patients with hypertension tend to have the preference to manage hypertension on their own, especially to use traditional or alternative medicines and herbs, such as cucumber, avocado leaves (Rahmawati & Bajorek, 2018), aloe vera (Yuliawati et al, 2021, celery leaves (Isnainy et al, 2021), cupping therapy (Darmawan et al, 2017), acupuncture (Hidayah et al, 2021), and others to replace the prescribed medication.…”
Section: Discussionsupporting
confidence: 86%
“…Herrera et al [7] found that hypertensive patients who drank 10 grams of HS petals daily could control mild to moderate hypertension as effectively as captopril. Similarly, Nikmah et al [24] suggested that the combination of antihypertensive medicines and HS petals could help the healing process more quickly. As we have stated above, HS is rich in phenolic acids and anthocyanins (esp.…”
Section: Mechanisms In the Treatment Of Hypertension By Hsmentioning
confidence: 99%
“…The mean systolic blood pressure decreased from 134 to 112.7 mmHg after the experimental duration. Nikmah et al [24] reported that HS had significant effect in the treatment of hypertension in postpartum mothers and benefited the healing process more quickly through a combination with antihypertensive medicines.…”
Section: Anti-hypertensive Efficacy Of Hsmentioning
confidence: 99%
“…The research result by Ritonga, Setiani, Umaroh, and Amri (2017) on 30 postpartum mothers in three General Hospitals, namely Ambarawa Hospital, Ungaran, and Semarang, found that the use of herbs proved to reduce blood pressure in postpartum mothers. The herbs used are Roselle Flowers (Hibiscus sabdariffa), dried roselle petals mixed with 200 ml of hot water at a temperature of 90°C.…”
Section: The Use Of Herbs For Postpartum Hypertensionmentioning
confidence: 99%